IMPORTANCE OF TEACHING ENGLISH FOR MILITARY STUDENTS - Dr. Nurmatova Guzal; Qarshibayeva Zebiniso (Galaxy International Interdisciplinary Research Journal, 2024)
The article discusses the role and opportunities of English language for military students. The importance and reasons of learning English of cadets are explained.